2010
DOI: 10.1088/0960-1317/20/8/085040
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-level assembly and sealing of a MEMS nanoreactor forin situmicroscopy

Abstract: This paper presents a new process for the fabrication of MEMS-based nanoreactors for in situ atomic-scale imaging of nanoparticles under relevant industrial conditions. The fabrication of the device is completed fully at wafer level in an ISO 5 clean room and it is based on silicon fusion bonding and thin film encapsulation for sealed lateral electrical feedthroughs. The fabrication process considerably improves the performances of previous nanoreactors. The wafer-level assembly allows faster preparation of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…4. The local pressure is measured from ∼1.0 to 2.2 atm (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) in N 2 gas, with ∼0.2 atm (3 PSI) steps. From the polar average of the FT for each image summarized in (a), one can see that the spacing of the outer set of Thon rings (upper window) increase with increasing pressure, while the spacing of the inner set of Thon rings decreases slightly (the spacing changes non-linearly with Δf, and most dramatically as Δf-0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4. The local pressure is measured from ∼1.0 to 2.2 atm (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) in N 2 gas, with ∼0.2 atm (3 PSI) steps. From the polar average of the FT for each image summarized in (a), one can see that the spacing of the outer set of Thon rings (upper window) increase with increasing pressure, while the spacing of the inner set of Thon rings decreases slightly (the spacing changes non-linearly with Δf, and most dramatically as Δf-0).…”
Section: Discussionmentioning
confidence: 99%
“…To simulate operando conditions for many relevant systems, higher pressures are needed: the decomposition temperature of PdO in O 2 , for instance, changes by nearly 300 degrees between 1 mbar and 1 atm [7][8][9]. There have been several reports of greater-than-atmospheric pressures using customized stages in which the gas is contained between two semi-transparent windows, typically a pair of amorphous SiN membranes separated by less than 100 mm [10][11][12][13][14][15][16][17]22,23]. The various commercial and custom-built systems that have been employed share basic operational principles, but vary in the details of design and implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The past few years have seen a flare of efforts to develop devices that allow real-time, in situ imaging of dynamical, nanoscale processes in fluids with the resolution of a TEM or STEM (scanning TEM) [1][2][3][4][5][6][7][8][9][10][11][12]. Liquid-cell TEM-STEM devices confine a thin slice of liquid sample in a sealed chamber sandwiched between two electron-transparent membranes, thus preventing evaporation while allowing the electron beam to pass through the sample to produce an image.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic reaction is performed inside the TEM using a nanoreactor which is very thin and transparent enough to enables the live imaging of the reaction. In the development of in-situ TEM different type of nanoreactors has been produced based on MEMS technology [1][2][3].Loading the nano particles into a nanoreactor can be problematic due to surface charge, uniformity of particle size distribution and the design of the nanoreactor. In order to study the behavior of particle motion in the nanoreactor, a qualitative flow visualization of colloidal polystyrene suspension in the nanoreactor was analyzed.…”
mentioning
confidence: 99%
“…The disappeared with time as the flow of the suspension continues. The dried nanoreactor showed that many particles were present on the heating area.The second nanoreactor was fabricated by surface micromachining [3]. The 3D sketch of the device is shown in Figure 2.…”
mentioning
confidence: 99%